Global bioanalytical support. (May 2014) - John Lin, Zhongping; Zhang, Tianyi; Pasas-Farmer, Stephanie; Brooks, Stephen D; Moyer, Michael; Connolly, Ron
With the globalization of drug development, there is an increasing need for global bioanalytical support. Bioanalysis provides pivotal data for toxicokinetic, pharmacokinetic, bioavailability and bioequivalence studies used for regional or global regulatory submission. There are many known complications in building a truly global bioanalytical operation, ranging from lack of global regulatory guidelines and global standard operating procedures to barriers in regional requirements on sample shipping, importation and exportation. The primary objective of this article is to discuss common experiences and challenges facing the biopharmaceutical industry when providing bioanalytical support in a global setting. The key components of global bioanalytical services include the supporting infrastructure, spanning project management, IT support of data management, best practices in bioanalytical method transfer and sample analysis, and comprehensive knowledge of the requirements of bioanalysis guidelines and differences in these guidelines. A case study will highlight best practices for successful management of a global project.